Eryptosis in autoimmune haemolytic anaemia. (30th October 2017) - Bartolmäs, Thilo; Mayer, Beate; Balola, Abdelwahab H.; Salama, Abdulgabar
Abstract: Objective: Haemolysis and anaemia related to autoimmune haemolytic anaemia (AIHA) of warm type (wAIHA) and of cold type (cAIHA) are believed to be solely due to antibody and/or complement‐mediated destruction and clearance of red blood cells (RBCs). There is evidence that RBCs of affected patients may also undergo eryptosis, the suicidal death of RBCs. Method: RBCs from 24 patients with wAIHA, 7 patients with chronic cAIHA and one patient with AIHA of mixed type were analysed for exposed phosphatidylserine (PS) by treatment with phycoerythrin‐labelled Annexin V, and cell‐associated fluorescence was measured using a MACSQuant flow cytometer. Results: PS‐exposing RBCs were detected in 7 of 13 patients with clinically significant wAIHA. Haemolysis was mostly related to IgM or IgA autoantibodies (aab) in those patients. In contrast, PS exposure in 11 patients with wAIHA in complete remission was comparable to that in healthy blood donors. All patients with chronic cAIHA and the patient with AIHA of mixed type showed haemolytic activity and high numbers of PS‐exposing RBCs. Patients with decompensated AIHA appear to respond to treatment with erythropoietin, which is a known inhibitor of eryptosis. Conclusion: Eryptosis may frequently occur in AIHA related to IgM or IgA aab. Inhibition of eryptosis with erythropoietin may represent a new therapeutic option in the treatment of AIHA.